2016
DOI: 10.1002/ejic.201690029
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover: Advanced Complex Inorganic Nanomaterials (Eur. J. Inorg. Chem. 13‐14/2016)

Abstract: The inside cover picture shows the reduction of the size of coherent domains in a spin‐crossover metal coordination polymer upon thermal cycling. The length of the domains displays a continuous decrease when the number of successive high‐spin/low‐spin/high‐spin sequences increases. This observation reveals an irreversible structural fatigability, indicating a potential break in the 1D‐chain morphology, and therefore sheds new light on a deeply investigated family of switchable materials. Details are discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…[15] One of the rare reported investigations, however, concerned the present compound and showed, first, that it is possible to extract reliable sizes and morphologies of coherent domains in these materials and, secondly, that SCO can engender a mechanical fatigability. [15,16] The present study aims to provide new information on the microstructural properties of the title SCO material in the form of a crystalline powder.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…[15] One of the rare reported investigations, however, concerned the present compound and showed, first, that it is possible to extract reliable sizes and morphologies of coherent domains in these materials and, secondly, that SCO can engender a mechanical fatigability. [15,16] The present study aims to provide new information on the microstructural properties of the title SCO material in the form of a crystalline powder.…”
Section: Introductionmentioning
confidence: 85%
“…Note that this kind of refinement has already been used and validated in a precedent study of the same sample. [15] This previous study, however, focused on one sample only. It was found that the coherent domains are cylindrical with their axis corresponding to the axis of the [Fe(Htrz) 2 (trz)] + chains.…”
Section: Morphologies Of the Coherent Domainsmentioning
confidence: 96%
See 1 more Smart Citation
“…As suggested by Colacio et al, the most plausible explanation for this phenomenon would be an enhanced photobleaching of the luminophore in the HS phase at high temperatures. Nevertheless, we cannot exclude the possibility of irreversible structural and/or morphological changes in the SCO complex itself in this temperature range,, which might lead to enhanced nonradiative relaxation of the excited luminophores. Another intriguing feature is that the spin‐transition temperatures in the luminescence measurements were found to be systematically different, in comparison with those observed in the magnetic measurements.…”
Section: Resultsmentioning
confidence: 92%
“…The spin‐transition temperature in the heating mode (T 1/2 ↑) was found to be 383 and 370 K for the first and second cycles, respectively. The difference between the first and the second cycle is commonly observed for this complex and might be associated with a structural and/or morphological reorganization , . (Notably, the complex does not contain solvent molecules, and thus, the effect of the solvent on the spin‐crossover properties can be discarded.)…”
Section: Resultsmentioning
confidence: 99%